The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.17509/ijal.v7i3.9798
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Critical Literacy as a Pedagogical Approach to Teaching English in Indonesia

Abstract: In English-as-a-Foreign-Language (EFL) context, critical literacy as an alternative approach to teaching language and literature may be considered as something new, compared to its origin in some English-speaking countries such as Australia or the USA. Teachers wishing to adopt critical literacy stance in their class are often left with little knowledge or experience on what critical literacy is and how to develop this approach in their class. This article discusses the result of a survey involving twenty one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 16 publications
0
50
0
3
Order By: Relevance
“…However, before promoting the importance of applying critical literacy to students, it is better to know the extent of the teachers" beliefs and knowledge of the critical literacy itself. In line with this, Gustine (2018) found that the majority of teachers still confused with what critical literacy is and how to create and a critical classroom. Whereas, the fact is in conducting a critical-oriented class, the starting point is the teacher should become critically literate to open space for students to be critical (McDaniel, 2006;McLaughlin & Allen, 2002;Riley, 2015).…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…However, before promoting the importance of applying critical literacy to students, it is better to know the extent of the teachers" beliefs and knowledge of the critical literacy itself. In line with this, Gustine (2018) found that the majority of teachers still confused with what critical literacy is and how to create and a critical classroom. Whereas, the fact is in conducting a critical-oriented class, the starting point is the teacher should become critically literate to open space for students to be critical (McDaniel, 2006;McLaughlin & Allen, 2002;Riley, 2015).…”
Section: Introductionmentioning
confidence: 71%
“…Related to teacher knowledge, they considered that their knowledge of critical literacy was very lack and it might have an impact on the teaching and learning process. In line with this, Gustine (2018) argues that English language teachers still have few knowledges about what critical literacy is and how to apply it in English classes. Whereas, in an effort to apply critical literacy in the classroom, it is teachers who become the starting point for the successful implementation of critical literacy itself, since teachers can help students to become critical readers and provide space for students to develop their critical abilities (McDaniel, 2006).…”
Section: The Teachers' Expectation In An Effort To Develop Criticamentioning
confidence: 96%
See 2 more Smart Citations
“…The school literacy movement is one of the efforts undertaken by the Indonesian government at this time, in addition to replacing the existing curriculum in schools. The Government of Indonesia through the Ministry of Education and Culture Regulations applies a movement in the form of school literacy which is carried out 15 minutes before lessons are conducted in class at the beginning of learning (Damaianti & Mulyati, 2017;Gustine, 2018). It is hoped that through the school literacy movement it can improve the quality of Indonesia by increasing students' interest in reading at school.…”
Section: Introductionmentioning
confidence: 99%